The Relevance of Eyebrow-Making Techniques to Facial Aesthetics and Contemporary Beauty Trends: A Literature-Based Analysis - Eti Juhaeti; Agus Ridwan Misbahuddin (Research, Training and Philanthropy Institution Natural Aceh, 2026)
This study analyses facial aesthetics through eyebrow-shaping techniques within contemporary beauty trends and their implications for cosmetology education. A systematic literature review following PRISMA was conducted on 32 Scopus and SINTA-indexed articles published from 2016 to 2025. Searches were performed in Scopus, SINTA, and Google Scholar using keywords combining facial aesthetics, eyebrow anatomy, microblading, and cosmetology education. Synthesis findings indicate that eyebrows play a central role in facial expression and proportion; ideal eyebrow position is slightly above the orbital rim in women and at or above the rim in men, with sex differences in thickness and arch. There is no universal eyebrow shape; aesthetic success depends on fit with facial structure, proportional balance, and individual preference. The review also identifies risks of overcorrection in corrective procedures and underscores the need to integrate anthropometric analysis into training. This study contributes a conceptual framework that integrates anthropometry, orbital anatomy, and eyebrow-shaping practice as a foundation for vocational curricula. Further research should test the module and validate assessment instruments.